2019
DOI: 10.1111/ipd.12566
|View full text |Cite
|
Sign up to set email alerts
|

Digital versus conventional impression method in children: Comfort, preference and time

Abstract: Background The comfortness and effectiveness of digital and conventional impression methods in children have not yet been compared. Aim To assess the digital and conventional impression methods in children in terms of comfort, preference, and the time required to take impressions. Design Digital impressions were taken by using an intraoral scanner, and conventional impressions were taken by using alginate from 28 patients by the same operator. In each impression‐taking‐process, comfort was assessed by both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
81
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(92 citation statements)
references
References 27 publications
7
81
1
3
Order By: Relevance
“…Compared with the conventional methods, acquiring a digital impression using an intraoral scanner has the advantages of easy repetition, direct model visualization, improved time efficiency, and chairside data acquisition for CAD/CAM prosthetics. Patients also show a strong preference for digital impression acquisition over the conventional methodology in the clinical setting [7]. The digital technique also plays a significant role in treatment planning via simulation in the aesthetic area.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the conventional methods, acquiring a digital impression using an intraoral scanner has the advantages of easy repetition, direct model visualization, improved time efficiency, and chairside data acquisition for CAD/CAM prosthetics. Patients also show a strong preference for digital impression acquisition over the conventional methodology in the clinical setting [7]. The digital technique also plays a significant role in treatment planning via simulation in the aesthetic area.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding comfort and preference over different methods, a recent study has shown that digital molding was considered more comfortable compared to the conventional alginate method and was considered the preferred method. [10] This study concluded that there was no statistically significant difference between the conventional molding and digital molding, concerning the time required for the technique. was also done in the present work, but the volunteers were adults.…”
Section: Discussionmentioning
confidence: 81%
“…[6,[14][15][16][17] Thus, direct intraoral scanning is an important tool for obtaining study models and analysis of dental measurements for children and young patients, since satisfaction with this method has already been shown to be higher in adults [18] and children. [10] However, more studies are still needed, especially clinical ones, since most studies in the literature analyze the accuracy of this method in resin models [13,17] so that it can be used in the same way as models obtained via conventional molding without harming future clinical conducts.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the operators were evaluated separately, there were significant differences. Unlike this study, similar studies that evaluated impression time 5,8,9,11,32 had operators experienced either in conventional or digital techniques. Furthermore, previous studies used complete impression technique, 6,8,9,32 regional impression technique for single implant 3,5,8 or different impression techniques (closed‐mouth technique) 31 comparing conventional impressions and digital scans.…”
Section: Discussionmentioning
confidence: 97%
“…Intraoral scanners (IOS) are increasingly used in dentistry for digital scans which avoid the challenges in clinical and laboratory steps of conventional techniques and improve patient comfort. Also, the scans and bite registrations can be digitally stored 2–12 . However, higher cost of the IOS and software and the learning curve are disadvantages of digital scanning, 10,13 and conventional impressions are still more commonly used 10,14–16 …”
mentioning
confidence: 99%